2022
DOI: 10.1007/s11356-022-23975-w
|View full text |Cite
|
Sign up to set email alerts
|

Combining voltammetric and mass spectrometric data to evaluate iron organic speciation in subsurface coastal seawater samples of the Ross sea (Antarctica)

Abstract: Iron (Fe) is the most important trace element in the ocean, as it is required by phytoplankton for photosynthesis and nitrate assimilation. Iron speciation is important to better understand the biogeochemical cycle and availability of this micronutrient, in particular in the Southern Ocean. Dissolved Fe (dFe) concentration and speciation were determined in 24 coastal subsurface seawater samples collected in the western Ross sea (Antarctica) during the austral summer 2017 as part of the CELEBeR (CDW Effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Harmful algal blooms formed by diatoms showed that the supply of iron (Fe) played a critical role in the development of extensive diatom blooms in coastal upwelling regimes (Bruland et al 2001). In addition, Fe, as a micronutrient required for phytoplankton growth, contributed to the marine primary productivity and carbon export (Vivado et al 2022). However, the concentration of Fe in seawater, especially in surface seawater was very low (Hogle et al 2018), and Fe deficiency in seawater limited the photosynthesis and growth of phytoplankton, resulting in insufficient utilization of nitrogen (Bruland et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Harmful algal blooms formed by diatoms showed that the supply of iron (Fe) played a critical role in the development of extensive diatom blooms in coastal upwelling regimes (Bruland et al 2001). In addition, Fe, as a micronutrient required for phytoplankton growth, contributed to the marine primary productivity and carbon export (Vivado et al 2022). However, the concentration of Fe in seawater, especially in surface seawater was very low (Hogle et al 2018), and Fe deficiency in seawater limited the photosynthesis and growth of phytoplankton, resulting in insufficient utilization of nitrogen (Bruland et al 2001).…”
Section: Introductionmentioning
confidence: 99%